Law Enforcement Against Psychotropic Narcotic Drug Abuse Through Medical Rehabilitation - Hermawanto; Maharani, Annisa Fitri; Fikri, Ahmad Ma’mun (Research Horizon, 2025)
This research employs a normative legal approach to critically analyze Indonesia's drug law enforcement, emphasizing the urgent need for rehabilitation over punitive measures for drug users. By examining existing legal frameworks and international conventions, the study highlights the misclassification of drug users as criminals rather than victims in need of support. The findings reveal that current policies disproportionately penalize users, often neglecting their human rights and the potential for rehabilitation. The research advocates for a paradigm shift in Indonesia's drug policy, proposing a balanced legal approach that prioritizes medical and social treatment for addicts. It underscores the importance of integrating rehabilitation into the legal framework, ensuring that drug users receive appropriate care rather than harsh penalties. This approach not only aligns with global standards but also addresses the growing prevalence of drug abuse in Indonesia. Ultimately, the study aims to influence policymakers to adopt more humane and effective strategies that protect the rights of drug users while combating drug-related crimes. By fostering a legal environment that supports rehabilitation, Indonesia can better address the complexities of drug abuse and promote public health.